Comportamento reológico e propriedades emulsificantes de um sistema misto constituído por proteínas de soro lácteo e amido - Sufra, Jethro (2022)
Whey has long been considered waste. However, it is rich in high-biological value proteins. In addition, in the form of concentrate, it can be mixed with starch to improve its functional properties and, therefore, be used more efficiently in the food industry. Mixing them may vary depending on certain conditions specific to the type of starch used. This research aimed to evaluate the effect of adding whey protein concentrate to three different types of starch (sweet cassava starch - PVD, sour cassava starch - PVA, and corn starch AM) on the rheological characteristics and emulsifying properties of the mixtures. The protein concentration was established at 2.5% (W/V) and the starch concentrations were 0%, 2.5%, 5.0%, and 7.5% (W/V). The centesimal composition (moisture content, lipids, proteins, carbohydrates, ash), pH, and rheological behavior were determined, and the microstructure was analyzed using scanning electron microscopy. The emulsions were characterized for emulsifying capacity, stability, and microstructure by fluorescence microscopy. The starch content influenced the apparent viscosity of the mixtures. The protein in the concentration of 2.5% presented no marked effects on the viscosity and flow behavior of the mixture, apart from PVD, for which the presence of protein contributed to a significant increase. The microstructure of the gels varies depending on the type and concentration of starch and the presence of protein. AM forms opaque and irregular gels, while PVD and PVA gels are more regular, less opaque, and with more pores. The presence of protein contributes to strengthening the structure of the gels. The emulsifying capacity of the mixture increases with increasing starch concentration, especially for AM. The presence of 2.5% starch in the mixture contributes to obtaining an emulsion of greater stability than the pure protein solution. The emulsion stability was reduced due to depletion flocculation for 5% and 7% starch concentrations. The mixture of WPC with PVD was the most indicated for the viscosity increase. On the other hand, the mixture with PVA was more suitable for forming stable emulsions. The improvement of the rheological and emulsifying properties resulting from the mixture of starch and whey protein concentrate depends on the latter’s concentration, the type of starch, and other parameters to be considered, such as pH.